Comorbidities of Chronic Obstructive Pulmonary Disease and Their Affect on Hospitalization of Patients in a Tertiary Care Hospital. Issue 1 (2nd January 2021) - Sridhara, Venkata Sai Hari Kalyan; Acharya, Vishak
ABSTRACT: Introduction : COPD is an obstructive airway disease with significant systemic comorbidities that affect hospitalization and the overall severity of the disease. The aim of the study was to assess the prevalence of comorbidities and their effect on the hospitalization of COPD patients. Methods : The study was a cross-sectional study conducted in 2013 among patients of a tertiary care hospital. The sample size was 106. Inclusion criteria were diagnosed patients of COPD according to GOLD criteria. Patients were diagnosed with COPD based on GOLD criteria guidelines and evaluated for various comorbidities based on presenting complaints. Variables collected were the number and kind of diagnosed comorbidities, the average number of hospitalizations per year. The prevalence of each comorbidity was found out and the chi-square test (p < 0.05) was used to find out the correlation between hospitalization and comorbidities. Results : Of 106 participants, 63.2% had at least 1 comorbidity. 37.73% had 2–4 comorbidities. Prevalence of diabetes mellitus was 35.8%, systemic hypertension was diagnosed in 47% of the subjects. 5.7% had left heart abnormalities, 4.7% had ischemic heart disease (IHD), and 16% had pulmonary arterial hypertension. 43.4% had gastroesophageal reflux disease and gastric ulceration, 38.6% had metabolic syndrome and 8.5% had obstructive sleep apnea, 8% had psychiatric disorders, 7.5% had osteoporosis, and 1.9% were diagnosed with lung malignancy. There was a significant association between mean hospitalizations and the presence of comorbidities (p < 0.05). Hospitalizations were majorly due to exacerbation of COPD. Conclusion : Prevalence of comorbid conditions among COPD patients are concluded to be high with an adverse effect on the average number of hospitalizations per year.